2022
DOI: 10.3389/feart.2022.1016491
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation of sentinel-1A interferometric decorrelation using vegetation index

Abstract: Sentinel-1A data are widely used in interferometric synthetic aperture radar (InSAR) studies due to the free and open access policy. However, the short wavelength (C-band) of Sentinal-1A data leads to decorrelation in numerous applications, especially in vegetated areas. Phase blurring and reduced monitoring accuracy can occur owing to changes in the physical and chemical characteristics of vegetation during the satellite revisit period, which essentially makes poor use of SAR data and increases the time and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…However, the above studies only qualitatively analyzed the impact of vegetation on InSAR deformation monitoring. Pan et al established a second-order linear model using NDVI and dualpolarization Sentinel-1 data, revealing and validating the relationship between C-band InSAR decorrelation and vegetation coverage [25]. Liu et al found the coherence with InSAR was logarithmically related to increasing NDVI [26].…”
Section: Introductionmentioning
confidence: 98%
“…However, the above studies only qualitatively analyzed the impact of vegetation on InSAR deformation monitoring. Pan et al established a second-order linear model using NDVI and dualpolarization Sentinel-1 data, revealing and validating the relationship between C-band InSAR decorrelation and vegetation coverage [25]. Liu et al found the coherence with InSAR was logarithmically related to increasing NDVI [26].…”
Section: Introductionmentioning
confidence: 98%